1983
DOI: 10.1007/bf00342785
|View full text |Cite
|
Sign up to set email alerts
|

Elimination and pharmacological effects following single oral doses of 50 and 75 mg of amitriptyline in man

Abstract: In a companion paper we described the disposition of a 75 mg single dose of amitriptyline in normal volunteers who were phenotyped as extensive or poor metabolizers of debrisoquine and bufuralol, and had a four-fold range in the oral clearance of the antidepressant, 50 mg of amitriptyline was also administered to the same volunteers. This paper compares the results after both doses and suggests that the disposition of amitriptyline is linear even in subjects with a low oral clearance. There was no relation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…N-demethylation of amitriptyline yields nortriptyline, an anti-depressant in its own right. Both amitriptyline and nortriptyline strongly bind to plasma proteins (Borga et al, 1969) and exhibit extensive tissue binding, evidenced by their high apparent volume of distribution (Schulz et al, 1983; Kornhuber et al, 1995; Lombardo et al, 2004). Further metabolization by CYP450 upon hydroxylation and glucoronidation results in inactivation followed by excretion in the urine (Rudorfer and Potter, 1987; summarized in Gillman, 2007).…”
Section: Amitriptylinementioning
confidence: 99%
“…N-demethylation of amitriptyline yields nortriptyline, an anti-depressant in its own right. Both amitriptyline and nortriptyline strongly bind to plasma proteins (Borga et al, 1969) and exhibit extensive tissue binding, evidenced by their high apparent volume of distribution (Schulz et al, 1983; Kornhuber et al, 1995; Lombardo et al, 2004). Further metabolization by CYP450 upon hydroxylation and glucoronidation results in inactivation followed by excretion in the urine (Rudorfer and Potter, 1987; summarized in Gillman, 2007).…”
Section: Amitriptylinementioning
confidence: 99%
“…Relatively little was previously known about the quantitative importance of direct glucuronidation for the elimination of AT in man in vivo. Schulz et al (1983) reported that only 2-5% of the given dose of AT (50 or 75 mg) was recovered in urine as AT and its glucuronide. Interestingly, in the study of Vandel et al (1982), a wide interindividual variation in the recovery of AT as conjugate was observed, the AT conjugate accounting for 3.4 to 57.7% (mean 26%) of the total recovery in urine.…”
Section: Discussionmentioning
confidence: 99%
“…Demethylation and hydroxylation are the major metabolic reactions (Bush and Harrier, 1983) and both amitriptyline and its first demethylation product, nortriptyline, accumulate in plasma during long-term treatment. However, only one published study has involved more than one dose level (Schulz et al, 1983).…”
Section: Introductionmentioning
confidence: 99%